2016
DOI: 10.1002/jib.370
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive composition and sensory evaluation of blended jambolan ( Syzygium cumini ) and sugarcane alcoholic fermented beverages

Abstract: The consumption of wine has increased considerably in recent years, which has aroused consumer interest in the consumption of alternative wines produced from various fruits. This study evaluates polyphenolic composition, identifies bioactive compounds and assays the total antioxidant capacity of four different formulations of jambolan (Syzygium cumini) and sugarcane fermented beverages (100:0, 70:30, 50:50 and 30:70), as well as their physical and chemical characteristics and also the sensory profile of the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
(35 reference statements)
0
7
0
2
Order By: Relevance
“…On order to expand the consumer market, it is necessary to develop new products with these fruits, e.g., jams, frozen pulps, cookies, food bars, ice cream, enriched flour, etc. (Carmo et al, 2012;Dias et al, 2003;Guedes et al, 2017;Dliveira et al, 2016;Santos & Silva, 2012;Silva et al, 2014a). Large amount of wastes, such as husks and seeds are discarded during the processing of fruits, and there is very little information on the exploitation of these by-products, thus, requiring further characterization.…”
Section: Introductionmentioning
confidence: 99%
“…On order to expand the consumer market, it is necessary to develop new products with these fruits, e.g., jams, frozen pulps, cookies, food bars, ice cream, enriched flour, etc. (Carmo et al, 2012;Dias et al, 2003;Guedes et al, 2017;Dliveira et al, 2016;Santos & Silva, 2012;Silva et al, 2014a). Large amount of wastes, such as husks and seeds are discarded during the processing of fruits, and there is very little information on the exploitation of these by-products, thus, requiring further characterization.…”
Section: Introductionmentioning
confidence: 99%
“…(also known as jamun, jambul, black plum or Indian blackberry) is a large evergreen tree of tropical as well as subtropical regions, belonging to Myrtaceae family rich in phenolic compounds (Tavares et al, 2016). It is indigenous to India as well as major parts of South-East Asia and was brought to Southern Africa for its edible fruits (Baliga et al, 2011;Oliveira et al, 2016). Additionally, jambolan is also found in Bangladesh, Pakistan, Nepal, Sri Lanka, Indonesia, Malaysia, Burma, South America and Eastern Africa Ayyanar & Subash-Babu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of minerals present in the sugarcane juice can be linked to the harvest process. One factor that could confound this analysis may be soil dust attached to the cane while it was processed (Oliveira et al 2016) and through the filtration process, which could have retained some mineral particles. Rakkiyappan et al (2003) reported an average ash content for mid-late sugarcane clones of 0.398 g per 100 g.…”
Section: Characteristics Of Raw Materialsmentioning
confidence: 99%
“…However the fiber content found in this study was very low (0.03 ± 0.0 g per 100 g of total fiber). Variations in the chemical composition of a food or beverage can occur for various reasons such as differences between varieties, cultivation conditions, harvest period, and industrial operations such as extraction and filtration (Oliveira et al 2016).…”
Section: Characteristics Of Raw Materialsmentioning
confidence: 99%